Plastic recycling : technical and economical evaluation of two different recycle loops - Diego Luna Victoria Torres (2024)
In this work, two different recycling loops for plastic waste are investigated regarding technical and economic aspects. The aim of the processes is to produce light olefins (ethylene and propylene), which serve as feedstock for the production of polyolefins. The loops are referred as chemical recycling and combustion loop. The chemical recycling loop consist of the pyrolysis of plastic waste with a product recovery section, in which the pyrolysis gas is treated to yield the olefin product. The combustion loop involves a more complex process, consisting of the incineration of plastic waste, with a subsequent flue gas cleaning process and a carbon capture unit, in which the CO2 of the flue gas is captured to produce methanol through CO2 hydrogenation. Afterwards, the crude methanol product is further processed in a methanol to olefins (MTO) unit, in which the olefin products are recovered after a hydrocarbon fractionation process. The results show that the combustion loop provides a better product yield and a lesser carbon footprint that the pyrolysis loop, with a selectivity of 79 wt.% compared to the 49 wt.% of the chemical recycling loop. The gap between the product yields becomes especially noticeable when the propylene yields are compared, then the combustion loop produces almost twice the amount of propylene that the chemical recycling loop. Regarding the ethylene yield and the produced CO2, although the combustion loop performance is better, the results lie on a similar range. However, when it comes to the capital cost and the energy demand, it comes out that the combustion loop requires much higher investments costs and amounts of energy. The results show that the combustion loop requires 52 times the power demand and 3 times the investment of the chemical recycling loop. The biggest issue in the combustion loop is the hydrogen demand for the CO2 hydrogenation. This demand is covered by a Electrolyzer, which is the most expensive and simultaneously the most energy consuming unit in the loop.